Produção e qualidade do leite em fazendas com certificação orgânica no nordeste dos Estados Unidos - Galvão Júnior, Jose Geraldo Bezerra (2017)
The objective of this study was to evaluate milk production performance and quality in 14 organically certified dairy farms in 05 states in the northeastern United States, through the evaluation of 14,246 records of monthly tests, with information on production and mammary gland health of Holstein (HO), Jersey (JE) and Holstein-Jersey cross-bred (XX) cows, in the period from May/2012 to June/2015. The number of lactating cows in the herds (mean ± standard deviation) was 38 ± 18. Milk yield (MY) and milk constituents were 21.33 ± 8.04 kg/animal/day, milk protein concentration (MPY) was 3.28 ± 0.45%, milk fat concentration (MFC) was 4.26 ± 0.98% and linear somatic cell count score (SCCS) was 2.54 ± 1.80 ~ SCC = 73 ± 44 x 10³ cells/mL. Milk production and composition and health of the mammary gland among the cow breeds were evaluated in the seasons and grazing season (GS) and non-grazing season (NGS) in the Northeastern region of the United States. Among the seasons of the year, MY was higher in the spring (22.51 kg/day) (P<0.05), being higher by 1.04, 1.58 and 1.96 kg/day compared to winter, summer and autumn, respectively. SCCS was higher in the summer (SCCS = 2.60 ~ SCC = 76 x 10³ cells/mL) (P<0.05) and lower in the spring (SCCS = 2.44 ~ SCC = 68 x 10³ cells/mL). Regarding the breeds, MY and milk corrected to 4% fat (4% FCM) presented better and significant (P<0.05) performance in HO, followed by XX and JE. SCCS was higher in HO (P<0.05), and it did not differ between JE and XX. In the GS, the variables MY and 4% FCM were higher than in the NGS. Only MFC had a higher and significant mean (P<0.05) in the NGS compared to the GS. Milk yield losses were estimated as a function of somatic cell counts in milk, considering the effects of cow breed, parity (primiparous or multiparous) and lactation stage. MY losses corresponded to 0.47 kg/day (2.4%) of lactation, equivalent to 150 kg in 320 days of lactation. Estimated losses between HO, JE and XX were 0.32 kg/day (2.04%), 0.26 kg/day (2.83%) and 0.27 kg/day (1.09%), respectively. Estimated losses were higher in multiparous cows 0.40 kg/day (2.59%) compared to primiparous 0.16 kg/day (1.27%), although, estimated losses were higher in primiparous cows during the first 30 days of lactation. The decrease in MY was more pronounced in the first 30 days post-partum, and at the end of lactation for all effects. The results obtained demonstrate the importance of observing the effects of seasonality, breed, grazing season, number of lactations and lactation stage in milk production and composition, and health of the mammary gland in herds under organic management in the study region, and they can be used as a tool to adjust herd management and to obtain better indexes of milk production and quality, reducing productive losses associated with mastitis